Revolutionary passage : from Soviet to post-Soviet Russia, 1985-2000 - Garcelon, Marc, 1958- (Politics, history, and social change., 2005)
From perestroika to Putin: a recent history of Russia's turbulent transformation from communist to post-communist nation.